Prophylactic and Therapeutic Indications for Third Molar Extractions as Compared to Observation and Conservative Management: A Systematic Review and Meta-Analysis - Alexandros Louizakis; Dimitris Tatsis; Theodoros Grivas; Sofia Tilaveridou; Ioannis Tilaveridis; Athanassios Kyrgidis (Surgeries)
Background: Third molar (M3) removal is considered one of the most frequent oral surgical procedures worldwide. Indications for extraction include both prophylactic and therapeutic reasons. However, this does not come without complications, and despite the widespread practice, there is no consensus on whether prophylactic M3 extraction is more beneficial than conservative management. Aims: The aim of this systematic review is to highlight and compare the main differences and outcomes between prophylactic and therapeutic removal of third molars with conservative treatment and observation. Several factors have been considered such as post-surgical infection risks and complications, hospitalization indications, economic factors and periodontal health of adjacent teeth. Methods: A literature review and meta-analysis were conducted, which comprises studies describing the incidence of postoperative complications, the periodontal status of the second molar (M2), the prevalence of caries, and the economic aspects of the M3 removal. Periodontal parameters of the adjacent teeth such as periodontal pocket depth (PPD) and clinical attachment level (CAL), as well as inferior alveolar nerve (IAN) damage and post-operative inflammatory complications such as bacteremia, were considered. Finally, hospitalization and the economic burden of this procedure were also stated. Results: Third molar retention is associated with increased periodontal disease such as PPD and accumulation of plaque to the adjacent teeth, as well as risk of caries. Contrarily, prophylactic M3 extraction is often linked to unnecessary morbidity and costs, such as risk of bacteremia, trismus, postoperative pain, IAN damage, and sometimes the need for hospitalization. From an economic aspect, this frequent procedure is mostly associated with higher direct and indirect costs, which can exceed the amount of EUR 1000 per patient without hospitalization. Conclusions: This review tried to determine whether the M3 observation and retention can be more beneficial than M3 extraction, after examining certain parameters. Findings indicate that unnecessary morbidity and costs can be attributed to third molar extraction, with postoperative complications such as pain and trismus and sometimes the need for hospitalization. Transient bacteremia also accompanies third molar removal.